Guided inquiry learning model application to train the students analysis skills on factors that affect reaction rate materials - Dhevira Aptia Firmanda; Dian Novita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The study aims to describe the applicability of learning model implementation, student activities, learning outcomes, students' analytical skills, and student responses with guided inquiry learning models application. The method used is one group pretest-posttest design with 24 students of XI IPA class. Research shows that (1) quality guided inquiry learning percentage during two meetings is 94.44% and 95.75%, respectively. (2) relevant student activity has an average percentage of 94.64%. (3) student learning outcomes in the factor that affects reaction rate material increases with n-gain scores obtained 83.68% in the high category. (4) the results of student analytical skills on each component with a high category n-gain score are element analysis was 95.83%, relationship analysis was 58.33%, and analysis of organizational principles was 79.17%. (5) the student response had very good category results with a percentage of 98.61%.ÃÂ